2008
DOI: 10.1590/s1517-70762008000200011
|View full text |Cite
|
Sign up to set email alerts
|

Specific surface area and structures of aluminas from fibrillar pseudoboehmite

Abstract: By heating powders of the aluminum monohydroxide fibrillar pseudoboehmite from 200 o C to 1400 o C several high surface area aluminas are prepared and characterized by X-ray diffraction and electron optical methods. Aqueous sols with pseudoboehmite fibrils of different lengths were dried by two methods: at room temperature and spray-dried. The following aluminas were obtained after treatment of the powders at increasing temperatures and having a range of specific surface areas: ). Spray-dried powders, fired at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Thus, we should concurrently investigate both for accurate interpretation of toxicity data (Teow et al 2011;Fadeel and garcia-Bennett 2010). In this study, short-AlNRs were more stable thermodynamically than long-AlNRs (Souza Santosa et al 2000;Vieira coelho et al 2008), and the surface area of long-AlNRs with high aspect ratio (thinner and longer nanorod-shaped morphology) was estimated to be approximately 54 % larger than that of short-AlNRs, although the primary particle size of long-AlNRs was larger than that of short-AlNRs. However, hydrodynamic diameters and surface charges of both types of AlNRs were similar within the biological vehicle used in this study.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, we should concurrently investigate both for accurate interpretation of toxicity data (Teow et al 2011;Fadeel and garcia-Bennett 2010). In this study, short-AlNRs were more stable thermodynamically than long-AlNRs (Souza Santosa et al 2000;Vieira coelho et al 2008), and the surface area of long-AlNRs with high aspect ratio (thinner and longer nanorod-shaped morphology) was estimated to be approximately 54 % larger than that of short-AlNRs, although the primary particle size of long-AlNRs was larger than that of short-AlNRs. However, hydrodynamic diameters and surface charges of both types of AlNRs were similar within the biological vehicle used in this study.…”
Section: Discussionmentioning
confidence: 80%
“…The textural properties of the supports used in this paper are displayed in Table 1. Supports designated as G and A have textural properties corresponding to the traditional values found in the literature for these kinds of aluminas (Vieira Coelho et al 2008). After the treatment at high pH with aqueous ammonia, the silica support (S) resulted in a solid with a high S BET and high porosity compared with the untreated Aerosil Degussa (65m 2 /g and 0.14 cm 3 /g, respectively).…”
Section: Resultsmentioning
confidence: 69%
“…The metallic Pt particle size of the spent Pt/(HZSM-48 + pseudoboehmite, 1:1) catalyst from the CO chemisorption increased to 6.5 nm compared to the metallic Pt particle size of 6.3 nm for the fresh catalyst, indicating that the sintering of Pt could be negligible during the MCP reforming reaction conditions. In addition, the phase transition from pseudoboehmite to aluminum oxide was not observed after catalytic test for 9 h. It has been reported that the phase transformation of pseudoboehmite occurs at a temperature higher than 470 • C [30].…”
Section: Ring Enlargement Reaction Of Methylcyclopentanementioning
confidence: 86%